Wear-resistant glaze and preparation method of wear-resistant ceramic tile
By adopting a high silicon and high aluminum system in the tile glaze, controlling the silicon-aluminum molar ratio and introducing specific oxides, building a high binding force skeleton structure, the problems of whitening and enlarging pores of the existing high aluminum glaze are solved, and the high wear resistance, Mohs hardness and good light transmittance of the tile are achieved.
Patent Information
- Application Number
- CN202510007519.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-03
AI Technical Summary
While the existing high-aluminum glaze improves the wear resistance and Mohs hardness of ceramic tiles, it is prone to whitening and enlarged pores, affecting light transmission and stain resistance.
The glaze formula with a high silicon and high aluminum system is adopted. By controlling the silicon-aluminum molar ratio between 3.2 and 3.8, α-Al2O3 and calcined zinc oxide are introduced, combined with monovalent potassium and sodium ions to replace part of divalent calcium and magnesium ions, a high binding force framework structure is constructed to enhance the vitrification degree and density of the glaze surface.
It significantly improves the wear resistance and Mohs hardness of the ceramic tiles, maintains high light transmittance and good stain resistance, avoids defects such as whitening and pores, and improves the comprehensive performance and visual effect of the glaze.
Smart Images

Figure BDA0005227365030000061 
Figure BDA0005227365030000071 
Figure BDA0005227365030000072
Abstract
Description
Technical Field
[0001] The invention relates to the field of building ceramics, and in particular to a preparation method of wear-resistant glaze and wear-resistant ceramic tiles. Background Art
[0002] There are ways to improve the wear resistance of glaze formula, such as increasing the aluminum content in the glaze. The addition of aluminum can indeed enhance the Mohs hardness and wear resistance of the glaze, but the Mohs hardness is usually below level 6, and the wear resistance is mostly level 4 below 2100 revolutions. In addition, high aluminum content will bring a series of new problems. For example, the glaze may appear white due to excessive aluminum, which weakens the transparency and visual beauty of the glaze. The light transmittance is between 15% and 24%. In addition, excessive aluminum content may also cause the pores to increase, affecting the density of the glaze, thereby reducing the stain resistance of the tile, making it easier for stains to embed into the surface of the tile, affecting its cleanliness and appearance in long-term use.
[0003] Therefore, how to improve the Mohs hardness and wear resistance of tiles while taking into account their light transmittance and stain resistance, and avoiding the problems of whitening and increased pores in traditional high-aluminum glazes, has become a key challenge in the field of ceramic materials. Summary of the invention
[0004] The main purpose of the present invention is to provide a wear-resistant glaze that meets the market's requirements for high wear resistance and Mohs strength of ceramic tiles while taking into account stain resistance and light transmittance, and avoids the problems of whitening and increased pores of traditional high-aluminum glazes. The secondary purpose of the present invention is to provide a method for preparing wear-resistant ceramic tiles.
[0005] To achieve the above object, the present invention provides a wear-resistant glaze, the raw materials of which, in terms of oxide mass fraction, include the following components: 2 47-51 copies, Al 2 O 3 22-25.1, K 2 O 2.3-2.8 parts, Na 2 O 2.4-2.8 parts, CaO 5-7.5 parts, MgO 1.3-2.1 parts, BaO 2.5-2.6 parts and ZnO 7.0-7.1 parts, Al 2 O 3 Medium α-Al 2 O 3 The weight parts are 18 to 21 parts.
[0006] The present invention proposes a glaze formula of a high-silicon and high-aluminum system, establishes a high-bonding skeleton structure, improves the bonding strength of the glaze surface, and controls the silicon-aluminum molar ratio to be approximately 3.2 to 3.8. 2 O 3Mainly introduced by corundum, the high silicon and high aluminum system of the present invention not only significantly improves the glass degree of the glaze, but also strengthens its hardness and density, and through this molar ratio, constructs a wear-resistant skeleton structure with high bonding force. In this structure, a large number of silicon oxygen tetrahedrons constitute the main grid, while aluminum oxygen tetrahedrons partially replace the position of silicon oxygen tetrahedrons, and are closely combined with the silicon oxygen network through shared oxygen atoms, and the uniform dispersion further improves the hardness of the glaze, giving the glaze extremely high wear resistance. At the same time, by reducing the content of calcium and magnesium in the glaze, by introducing a large amount of zinc and monovalent potassium and sodium ions in the form of calcined zinc oxide to jointly replace part of the divalent calcium and magnesium ions, the effect of poor color development and crystallization problems on the sense of transparency caused by excessive calcium and magnesium ion content is avoided; at the same time, cations such as sodium and potassium play an important regulatory role, balancing the charge of aluminum oxygen tetrahedrons, so that the entire network structure is both dense and maintains a certain toughness.
[0007] The reasonable ratio of silicon and aluminum is the key to achieving high performance of glaze. The increase of silicon promotes the formation of a more complete vitrified network on the glaze surface, greatly improves the density of the material, reduces the generation of pores, and thus significantly improves the hardness. The appropriate addition of aluminum enhances the wear resistance of the glaze and improves its mechanical strength, while preventing the brittleness problem caused by excessive vitrification. By balancing the synergistic effect of silicon and aluminum, this high-silicon and high-aluminum system not only gives the glaze surface stronger wear resistance, but also achieves a matte effect and improves the visual uniformity of the glaze surface. Through the construction of this high-bonding skeleton structure, the hardness of the glaze surface is greatly improved, while maintaining the stability and durability of the glaze structure.
[0008] The innovative formula of the present invention is not only superior to traditional glazes in mechanical properties, but also significantly improves the wear resistance and Mohs hardness of the glaze surface, and makes the brick surface matte and stain-resistant. It also avoids common glaze defect problems such as whitening, crystallization, and pores, and has excellent visual effects.
[0009] Preferably, the wear-resistant glaze raw materials include the following components in terms of oxide mass fraction: SiO 2 49.68 copies, Al 2 O 3 22.75 copies, K 2 O 2.34 parts, Na 2 O 2.70 parts, CaO 7.03 parts, MgO 1.80 parts, BaO 2.56 parts and ZnO 7.04 parts, Al 2 O 3 Medium α-Al 2 O 3 The weight proportion is 18 parts, and it has the best comprehensive performance in terms of tile glaze wear resistance, Mohs strength, light transmittance and glaze defect improvement.
[0010] The present invention also provides a method for preparing wear-resistant ceramic tiles, comprising the following steps:
[0011] S1, preparing a green body and drying the green body;
[0012] S2, applying the aforementioned wear-resistant glaze to the outermost layer of the body to form a wear-resistant glaze layer;
[0013] S3, firing in a kiln and polishing the surface of the ceramic tile.
[0014] Specifically, the glazing method in the scheme can be based on actual needs using known methods such as pouring, spraying and screen printing, and is not limited here.
[0015] Preferably, the wear-resistant glaze layer with a thickness of 0.05 to 0.10 mm is formed by screen printing in S2. The wear-resistant glaze layer can form a more uniform thin glaze film on the glaze layer through the thin screen printing technology, so that it can be quickly and evenly vitrified during the high-temperature melting process. The rapid vitrification of the thin glaze layer not only improves the density of the glaze surface, but also forms a hard microstructure, further enhances the hardness and wear resistance of the glaze surface, achieves high transparency of the glaze layer, and provides a reliable guarantee for the aesthetics and practicality of the glaze layer.
[0016] Specifically, in the selection of polishing method, when the thickness is less than 0.5 mm, it is preferably prepared by soft polishing or indirect polishing with abrasive liquid to avoid excessive polishing of the glaze surface.
[0017] Preferably, after preparing the green body in S1, the process further comprises step S101: applying a basic glaze and drying to form a basic glaze layer.
[0018] Further preferably, after forming the basic glaze layer in step S101, the method further comprises step S102: forming a decorative bottom layer by inkjet printing, screen printing or roller printing. The decorative bottom layer generally includes a pattern, texture, etc. preset on the brick surface.
[0019] Further preferably, the decorative base layer is formed by inkjet printing in S102; and after step S102, step S103 is also included: a preset three-dimensional pattern layer is formed on the flat printed layer by screen printing. Through the cooperation of the decorative base layer and the three-dimensional pattern layer, a micro-concave-convex surface is formed on the tile surface, which has a three-dimensional stacked decorative effect. Through the principle of stress dispersion and contact area reduction on the irregular surface, the degree of glaze scratches and the range of glaze damage can be reduced when an external object scratches the tile surface, thereby improving the wear resistance of the glaze surface. Combined with the light-transmitting wear-resistant glaze layer, the aesthetic effect of the glaze layer is further enhanced.
[0020] Preferably, the screen printing thickness in step S103 is 0.4-0.5 mm.
[0021] The present invention also provides a wear-resistant ceramic tile, which is prepared by any of the above-mentioned methods for preparing wear-resistant ceramic tiles, thereby having all the corresponding beneficial effects of the above-mentioned solutions, which will not be described one by one here.
[0022] Compared with the prior art, the present invention proposes an innovative glaze formula, providing a method of controlling the silicon-aluminum molar ratio between 3.2 and 3.8, wherein the raw material alumina is mainly α-Al introduced by corundum. 2 O 3 The invention discloses a high-silicon and high-aluminum glaze system, in which a large amount of zinc is introduced by calcining zinc oxide to jointly replace part of the divalent calcium and magnesium ions with monovalent potassium and sodium ions, thereby improving the wear resistance and Mohs hardness of the ceramic tile glaze, while maintaining the anti-fouling performance, improving the light transmittance and surface defects of the glaze layer, avoiding the problems of whitening and increased pores of traditional high-aluminum glazes, so that the wear resistance reaches level 4 and above 2100 revolutions, the Mohs hardness reaches level 6 and above, the light transmittance is above 21%, and the stain resistance reaches national standard level 5; the invention further proposes an innovation in the process of preparing wear-resistant ceramic tiles, by forming a micro-concave-convex surface on the tile surface or thin screen printing, the glaze performance of the prepared ceramic tile is further improved, so that the wear resistance of the ceramic tile surface reaches level 4 and above 6000 revolutions, while the Mohs hardness is ≥ level 7, and the light transmittance is between 21-28%, among which the best wear resistance reaches level 4 and above 9000 revolutions, and the best Mohs hardness can reach level 8. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0024] The present application proposes a wear-resistant glaze, the raw materials of which, calculated by oxide mass fraction, include the following components: SiO 2 47-51 copies, Al 2 O 3 22-25.1, K 2 O 2.3-2.8 parts, Na 2 O 2.4-2.8 parts, CaO 5-7.5 parts, MgO 1.3-2.1 parts, BaO2.5-2.6 parts and ZnO 7.0-7.1 parts, Al 2 O 3 Medium α-Al 2 O3 The weight parts are 18 to 21 parts.
[0025] The present application also provides a method for preparing wear-resistant ceramic tiles, comprising the following steps:
[0026] S1, preparing a green body and drying the green body;
[0027] S2, applying the aforementioned wear-resistant glaze to the outermost layer of the body to form a wear-resistant glaze layer;
[0028] S3, put into kiln for firing and polish the surface of the tile.
[0029] Preferably, in S2, a wear-resistant glaze layer with a thickness of 0.05 to 0.10 mm is formed by screen printing.
[0030] In a preferred embodiment, after preparing the green body in step S1, the process further comprises step S101: applying a basic glaze and drying the glaze to form a basic glaze layer.
[0031] In a preferred embodiment, after forming the basic glaze layer in S101, the process further includes step S102: forming a decorative base layer by inkjet printing, screen printing or roller printing.
[0032] In a preferred embodiment, the decorative base layer is formed by inkjet printing in step S102; after step S102, step S103 is further included: forming a preset three-dimensional pattern layer on the flat printing layer by screen printing. Preferably, the screen printing thickness in step S103 is 0.4-0.5 mm.
[0033] The technical scheme of the present invention is further described in detail below in conjunction with specific embodiments or comparative examples. In the following embodiments and comparative examples, raw materials, reagents, etc. not otherwise specified are all commercially available, and the same batch of raw materials or reagents are used in the embodiments and comparative examples; the preparation methods without special conditions are all prepared by conventional, well-known preparation methods.
[0034] 1. Experimental description of specific embodiments and comparative examples
[0035] 1.1 Some raw materials or processes in specific embodiments or comparative examples are described:
[0036] 1.1.1 Provide a basic glaze as an example. The basic protective glaze is made of existing raw materials. The chemical composition is calculated by weight percentage and meets the following requirements: SiO 2 40~45%;Al 2 O 3 20~25%;Fe 2 O 30.06~0.2%; CaO 4.0~6.0%; MgO 3.0~5.0%; K 2 O 1.0-4.0%;
[0037] NaO 1.0~3.0%; TiO 2 0.05~0.15%; BaO 4.0~12.0%; ZnO 1.5~2.5%; MnO<0.01%; P 2 O 5 <0.03%; SO 3 <0.015%; ZrO 2 <0.02%; SrO<0.03%.
[0038] 1.1.2 The sintering temperature in the specific embodiments or comparative examples is 1210-1215°C, and the sintering time is 65 minutes.
[0039] 1.1.3 In the specific embodiments or comparative examples, a polishing process parameter is provided as an example: a 240-mesh sponge head is used for indirect polishing with diamond polishing liquid.
[0040] 1.1.4 In the specific embodiments or comparative examples, the glaze is usually made of pure oxides, which can meet the requirements of the corresponding oxide raw materials by weight, including the following components: SiO 2 47-51 copies, Al 2 O 3 22-25.1, K 2 O 2.3-2.8 parts, Na 2 O 2.4-2.8 parts, CaO 5-7.5 parts, MgO 1.3-2.1 parts, BaO 2.5-2.6 parts and ZnO 7.0-7.1 parts. 2 O 3 The α-Al2O3 is introduced by corundum in an amount of 18 parts by weight. 2 O 3 .
[0041] In actual production, existing mineral raw materials are used for matching and adjustment, and the oxides in the mineral raw materials only need to meet the above-mentioned raw material weight requirements.
[0042] 1.2 Detection performance and test methods or standards
[0043] 1.2.1 Wear resistance
[0044] Testing standard: GB / T 3810.7-2016.
[0045] 1.2.2 Antifouling performance
[0046] Testing standard: GB / T 3810.14-2016.
[0047] 1.2.3 Mohs hardness
[0048] Detection method: Use diamonds of different hardness to scratch the surface of the material to be tested in turn, and observe the scratches to determine the hardness level of the material.
[0049] 1.2.4 Light transmittance
[0050] Testing standard: GB / T2680-94, by spreading glaze powder on blank powder, where the thickness of glaze powder is 5mm, the thickness of blank powder is 2mm, pressing it into blocks by a press, sintering in a kiln, discarding the blank and processing it into a 1mm thick sheet, and then measuring the direct transmittance of sunlight, the result is the transmittance.
[0051] 1.2.5 Color difference
[0052] Testing standard: GB / T 11186.3-1989.
[0053] Example 1
[0054] Provide ceramic tiles and conduct performance testing on ceramic tile surfaces.
[0055] The method for preparing ceramic tiles comprises the following steps:
[0056] S1: Pressing the body layer material into a tile forming blank, and then kiln drying to form a semi-finished blank;
[0057] S2: The semi-finished blank in S1 is coated with a basic glaze through a linear glazing machine to form a basic glaze layer, and then enters a drying kiln for drying;
[0058] S4: Printing patterns and textures on the surface of the dry brick surface by inkjet printing technology to form a decorative base layer;
[0059] S5: glaze the surface of the tile with a thickness of 0.30mm;
[0060] S6: Firing in kiln and polishing the surface of the tile.
[0061] The weight percentages and silicon-aluminum molar ratios of the glaze compositions of Examples 1-1 to 1-7 are shown in the following table:
[0062]
[0063]
[0064] Comparative Example 1
[0065] Ceramic tiles are provided, and the performance of the ceramic tile surface is tested. The specific preparation method and glaze composition of the ceramic tiles refer to Example 1-2, except that: the SiO 2 and Al 2 O 3 The weight fractions and the corresponding silicon-aluminum molar ratios are different. For specific comparative examples, refer to the following table:
[0066] Serial number <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[SiO 2 :Al 2 O 3 Molar Ratio]]> Comparative Example 1-1 45.95 25.64 3.04 Example 1-2 49.68 22.75 3.71 Comparative Example 1-2 51.68 19.27 4.55 Comparative Examples 1-3 52.90 16.86 5.32 Comparative Examples 1-4 52.97 13.64 6.59
[0067] The relevant properties measured in Examples 1-1 to 1-7 and Comparative Examples 1-1 to 1-4 are as follows:
[0068]
[0069]
[0070] From the above data comparison, it can be seen that when the wear-resistant glaze raw material composition of the present application is used as the glaze polishing raw material, and when the silicon-aluminum molar ratio is in the range of 3.2 to 3.8, it can be seen that the wear resistance in Examples 1-1 to 1-7 is above level 4, 2100 revolutions, the Mohs hardness reaches above level 6, the anti-fouling performance reaches the national standard level 5, the light transmittance is above 21%, and the glaze surface avoids whitening.
[0071] By comparing Example 1-2 with Comparative Examples 1-1 to 1-4, it can be seen that when the silicon-aluminum molar ratio is lower than 3.2, the Mohs hardness and light transmittance of the glaze are significantly reduced, and the overall performance is degraded. This may be due to the insufficient combination of silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons, the loose network structure, and the weakening of the bonding strength and degree of vitrification inside the glaze layer. For example, the silicon-aluminum molar ratio of Comparative Example 1-1 is 3.04. Although its wear resistance reaches level 4 at 6000 revolutions, the Mohs hardness is reduced to level 6, and the light transmittance is significantly reduced to 15%. Excessive aluminum oxide content will significantly increase the melting temperature of the glaze. If the firing temperature is insufficient or the time is insufficient, the glaze may not be fully melted, but the degree of vitrification is reduced, resulting in a rough glaze or incomplete firing. Excessive aluminum oxide may cause the glaze to form a microcrystalline structure during the cooling process, reduce the transparency of the glaze, and appear as a milky or turbid effect. On the contrary, when the silicon-aluminum molar ratio exceeds 3.8, too much silicon-oxygen tetrahedron causes the glaze to be over-vitrified, forming a brittle structure, thereby significantly reducing the wear resistance and mechanical strength. For example, the wear resistance of comparative examples 1-3 and 1-4 is 1500 at level 3 and 750 at level 3, respectively, which is significantly lower than 6000 at level 4 of embodiment 1-2. In addition, due to the insufficient content of aluminum-oxygen tetrahedron, the glaze skeleton structure is unbalanced, further weakening the stress performance of the glaze layer. Although the transmittance is improved at this time, the excessive degree of vitrification may cause the glaze to appear white, the visual effect is monotonous, and lacks a sense of hierarchy. Therefore, controlling the silicon-aluminum molar ratio between 3.2 and 3.8 can effectively balance the synergy of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron, and construct a stable and dense network structure. The glaze within this range not only has excellent wear resistance and Mohs hardness, but also can achieve an ideal balance between stress and transmittance, and comprehensively improve the comprehensive performance and visual effect of the glaze.
[0072] Example 2
[0073] Ceramic tiles are provided, and performance testing is performed on the ceramic tile surface. The specific preparation method and glaze polishing parameters of the ceramic tiles refer to Example 1-2, except that: Step S5 is glazing by screen printing.
[0074] Example 2-1S5 is a glaze polished by single screen printing, and the glaze thickness is 0.057 mm.
[0075] Example 2-2S5 is glazed by two screen printing processes, and the glaze thickness is 0.093 mm.
[0076] Example 2-3S5 is glazed by multiple screen printing, and the glaze thickness is 0.305 mm.
[0077] Serial number Wear resistance Mohs hardness Glaze color difference (△E) Example 1-2 Level 4 6000 rpm Level 7 1.90 Example 2-1 Level 4 9000 rpm Level 8 0.39 Example 2-2 Level 4 9000 rpm Level 8 0.93 Example 2-3 Level 4 6000 rpm Level 7 4.30
[0078] Note: Color difference test: Use a colorimeter to measure the brightness, red-green value and yellow-blue value changes before and after the tile glaze polishing process. Finally, the color difference value △E is used for evaluation (evaluation: △E≤2, good transparency, 2<△E≤5, average transparency, △E>5, poor transparency.
[0079] From the comparison of the above data, it can be seen that by comparing Example 1-2 with Example 2-1, it can be seen that the Mohs hardness and wear resistance of the glaze are further enhanced by thin screen printing compared with conventional glazing. By comparing Examples 2-1 to 2-3, it can be seen that when the screen printing thickness is about 0.05 to 0.1 mm, there is an obvious gain effect on the Mohs hardness and wear resistance, the wear resistance reaches level 4 at 9000 revolutions, the Mohs hardness reaches level 8, and the glaze has low color difference and good transparency. When the screen printing thickness reaches about 0.3 mm of conventional glazing, the glaze color difference increases significantly and the transparency decreases.
[0080] Example 3
[0081] Ceramic tiles are provided, and performance testing is performed on the ceramic tile surface. The specific preparation method of the ceramic tiles and the glaze polishing parameters refer to Example 1-2.
[0082] The difference is that the S4 process steps are different. In this embodiment, S4 is to print the surface patterns and textures of the dry brick surface by inkjet printing technology to form a decorative base layer; and then use screen printing to add some pattern points with a thickness of 0.4mm to form a slightly concave and convex surface.
[0083] The relevant properties detected in Examples 1-2 and Example 2 are shown in the following table:
[0084] Serial number Wear resistance Mohs hardness Scratch test Example 1-2 Level 4 6000 rpm Level 7 Scratches evenly distributed on the surface Example 3 Level 4 9000 rpm Level 7 Many scratches on the surface
[0085] Scratch test: Use a 100*100mm test brick surface, use a steel wool to scratch the test brick surface 200 times, rinse with water and observe the surface scratches. Evaluation: Evenly distributed scratches on the surface [the scratch area accounts for more than 60% of the test brick surface] / Many scratches on the surface [the scratch area accounts for 40-60% of the test brick surface] / Partial scratches on the surface [the scratch area accounts for 20-30% of the test brick surface] / Few or no scratches on the surface [the scratch area accounts for less than 20% of the test brick surface].
[0086] Comparing the data of Examples 1-2 and Example 3, it can be seen that the wear resistance and anti-scratch performance of Example 3 are significantly improved due to the formation of a micro-concave-convex surface.
[0087] Comparative Example 2
[0088] Ceramic tiles are provided, and the performance of the ceramic tile surface is tested. The specific preparation method of the ceramic tiles and the mass fraction of the raw materials refer to Example 1-2, except that: Al 2 O3 The composition is different
[0089] Comparative Example 2-1: No α-Al2O3 introduced from corundum is added to the alumina raw material. 2 O 3 ;
[0090] Comparative Example 2-2 α-Al2O3 introduced from corundum in the alumina raw material 2 O 3 The mass fraction is 15 parts;
[0091] Comparative Example 2-3 α-Al2O3 introduced from corundum in the alumina raw material 2 O 3 The mass fraction is 25 points.
[0092]
[0093] From the above data comparison, it can be seen that when α-Al is not introduced into the alumina raw material 2 O 3 (Comparative Example 2-1) or α-Al in the raw material 2 O 3 When the mass fraction of α-Al is less than 18 parts (Comparative Example 2-2), its wear resistance and Mohs hardness are significantly reduced, and the glaze effect is reduced. 2 O 3 When the mass fraction of is higher than 21, such as in Comparative Example 2-3, α-Al 2 O 3 The increase in the mass fraction has a greater improvement on the wear resistance and Mohs hardness, but the glaze surface appears white and the glaze is not melted. Similar tests have found that only when α-Al 2 O 3 When the mass percentage of aluminum oxide in the raw material is 18 to 21 parts, it can improve the wear resistance and Mohs hardness while maintaining better light transmittance and glaze effect, avoiding the phenomenon of whitening of the glaze and large pores or a large amount of pores.
[0094] Comparative Example 3
[0095] Ceramic tiles are provided, and the performance of the ceramic tile surface is tested. The specific preparation method of the ceramic tiles refers to Example 1-2, except that: the weight percentage of the raw materials for glazing, the specific adjustment instructions and the composition are as follows.
[0096] Comparative Example 3 is a high aluminum content glaze in the background technology, and its formula components are calculated in parts by weight.
[0097] Serial number <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> CaO MgO BaO ZnO Example 1-2 49.68 22.75 2.34 2.7 7.03 1.8 2.56 7.04 Comparative Example 3 47.59 17.63 0.62 0.47 6.55 13.49 0.34 8.22
[0098] The relevant properties obtained by testing the specific embodiments of Examples 1-2 and Comparative Example 3 are as follows:
[0099]
[0100] From the above data comparison, it can be seen that by comparing Examples 1-2 with Comparative Example 3, it can be seen that the wear-resistant glaze of the present application has significantly improved wear resistance from level 4 2100 revolutions to level 4 6000 revolutions, and the Mohs hardness has been significantly increased from level 5 to level 7, the glaze effect has been significantly improved, the light transmittance has been increased from 24.2% to 27.4%, and the anti-fouling performance has reached the national standard level 5.
[0101] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A wear-resistant glaze, characterized in that: The raw materials include the following components, calculated in parts by mass of oxides: 47-51 parts of SiO2, 22-25.1 parts of Al2O3, 2.3-2.8 parts of K2O, 2.4-2.8 parts of Na2O, 5-7.5 parts of CaO, 1.3-2.1 parts of MgO, 2.5-2.6 parts of BaO and 7.0-7.1 parts of ZnO, and the weight portion of α-Al2O3 in Al2O3 is 18-21 parts.
2. The wear-resistant glaze according to claim 1, characterized in that: The molar ratio of Si:Al in the wear-resistant glaze raw material component is 3.2-3.
8.
3. The wear-resistant glaze according to claim 1, characterized in that: The raw materials include the following components, calculated in parts by mass of oxides: 49.68 parts of SiO2, 22.75 parts of Al2O3, 2.34 parts of K2O, 2.70 parts of Na2O, 7.03 parts of CaO, 1.80 parts of MgO, 2.56 parts of BaO and 7.04 parts of ZnO, and the weight portion of α-Al2O3 in Al2O3 is 18 parts.
4. A method for preparing wear-resistant ceramic tiles, characterized in that: The following steps are involved: S1, preparing a green body and drying the green body; S2, applying the wear-resistant glaze as claimed in claim 1, 2 or 3 to the outermost layer of the body to form a wear-resistant glaze layer; S3, put into kiln for firing and polish the surface of the tile.
5. The method for preparing the wear-resistant ceramic tile according to claim 4, characterized in that: In S2, the wear-resistant glaze layer having a thickness of 0.05 to 0.10 mm is formed by screen printing.
6. The method for preparing the wear-resistant ceramic tile according to claim 4 or 5, characterized in that: After the green body is prepared in step S1, step S101 is further included: applying a basic glaze and drying to form a basic glaze layer.
7. The method for preparing the wear-resistant ceramic tile according to claim 6, characterized in that: After forming the basic glaze layer in S101, it also includes step S102: forming a decorative base layer by inkjet printing, screen printing or roller printing.
8. The method for preparing the wear-resistant ceramic tile according to claim 7, characterized in that: In S102, the decorative base layer is formed by inkjet printing. After step S102, step S103 is further included: forming a preset three-dimensional pattern layer on the decorative base layer by screen printing.
9. Wear-resistant ceramic tile, characterized in that: The wear-resistant ceramic tile is prepared by the preparation method of any one of claims 4 to 8.
Citation Information
Patent Citations
High-whiteness matte fine wear-resistant glaze, ceramic tile and preparation method of high-whiteness matte fine wear-resistant glaze
CN114716146A
High-white ground glaze, wear-resistant transparent glaze, wear-resistant full-polished glaze ceramic tile and preparation method
CN114920457A
Anti-slip protective glaze, anti-slip stain-resistant ceramic tile and preparation method of anti-slip stain-resistant ceramic tile
CN116282921A
Albite and / or anorthite glass ceramic material exhibing thermal warmth
WO2016155909A1